An update on the multimodality of localized rectal cancer. (December 2016) - Artac, Mehmet; Korkmaz, Levent; El-Rayes, Bassel; Philip, Philip A.
Highlights: A multidisciplinary team is essential in the management of localized rectal cancer. Pre-operative chemoradiotherapy is the standard for node-positive rectal cancer. Pre-operative chemoradiotherapy is associated with enhanced sphincter-preservation. 5-FU or its pro-drug capecitabine is standard for chemoradiotherapy. Abstract: New strategies have reduced the local recurrence (LR) rate and extended the duration of overall survival (OS) in patients with localized rectal cancer (RC) in recent decades. The mainstay of curative treatment remains radical surgery; however, downsizing the tumor by neo-adjuvant chemo-radiotherapy and adjuvant cytotoxic therapy for systemic disease has shown significant additional benefit. The standardization of total mesorectal excision (TME), radiation treatment (RT) dose and fractionation, and optimal timing and sequencing of treatment modalities with the use of prolonged administration of fluoropyrimidine concurrent with RT have significantly decreased the rates of LR in locally advanced rectal cancer (LARC) patients. This review focuses on the optimization of multi-modality therapies in patients with localized RC.